The Relationship between Knowledge Level and Attitude About Leucorrhoea with Vaginal Prevention Behavior in Adolescents - Nita Yulia, Eli; Umiastuti, Pirlina; Sudaryanti, Lestari (Jurnal KESANS : Kesehatan dan Sains, 2022)
Background: Adolescents are a population group aged 10-19 years. Knowledge and attitudes of young women about vaginal discharge affect the behavior of preventing vaginal discharge which aims to maintain the cleanliness of the genital organs. Normal physiological vaginal discharge is white or clear. Abnormal vaginal discharge is characterized by changes in color, consistency, volume, odor, and may be associated with symptoms of itching, pain, dysuria, pelvic pain, or intermenstrual or postcoital bleeding. Methods: This research method is an analytic observational cross-sectional. The number of samples was 107 students of class XI with a sampling technique using total sampling. The independent variable used is the level of knowledge and attitudes about vaginal discharge in SMA Negeri 1 Umbulsari, the dependent variable is the behavior of preventing vaginal discharge in adolescents at SMA Negeri 1 Umbulsari. The instrument used is a questionnaire. Data analysis includes univariate and bivariate analysis using the chi square test. Results: The results showed that most of the students' knowledge had a pretty good category of 64.5%. The attitude variable in the category of moderately agrees is 65.4%. The behavior of preventing vaginal discharge as much as 56.1% had good vaginal discharge prevention behavior. The results of thetest of the chi square relationship between knowledge and attitude towards whiteness p = 0.00 (p < 0.05). The relationship between vaginal discharge attitudes and vaginal discharge prevention behavior was p = 0.031 (p < 0.05). Conclusion: These data indicate that there is a relationship between the level of knowledge and the attitude of vaginal discharge and there is a relationship between attitudes and behavior to prevent vaginal discharge. Keywords: knowledge; attitude; behavior to prevent vaginal discharge